Assessment of phytoextraction potentials of three indigenous plant species in soil contaminated with spent engine oil - Azorji, Johnpaul Nnawuike; Nwachukwu, Udodi Chibuike; Nwachukwu, Michael Oluchukwu; Ugochukwu, Mmasi Godson; Dike, Kelechi Stanley; Nzenwa, Peter Odinaka; Igbokwe, Moses Chukwuebuka (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2024)
This study was carried out to evaluate the tolerance capacity of three plant species and to ascertain their phytoremediation potentials by pot culture experimentation. An equal volume of pre-sieved soil (20kg) was filled in Polythene bags and arranged at 0.5m spacing between polybags and 1m between replications and perforated at the base to avoid water logging. Concentrations of spent engine oil spiked included 0, 4%, 8%, 12% and 16% (v/w) which was allowed to stabilize for two (2) weeks to simulate the condition of the natural spill. The untreated soil served as a control. Twelve weeks after exposure, the plants were harvested and assayed for selected heavy metals using AAS. Results obtained showed that metal accumulation patterns were in the order C. odorat>A.africana>A.compressus. The results further showed that C. odorata and A. africana exhibited characteristics typical of a phytoextractor while A. compresses could be applied as a phytostabiliser of spent engine oil-polluted soils. It is recommended that the three-plant species be tried for phytoremediation of spent engine oil-contaminated soils.